PENGUATAN SIKAP DEMOKRATIS MELALUI PROBLEM BASED LEARNING (PBL) DENGAN MATERI NILAI-NIALI PANCASILA SEBAGAI DASAR NEGARA DIDUKUNG MANAJEMEN KELAS (GROUP SEATING) DAN SUPERVISI AKADEMIK UNTUK INTERAKSI BELAJAR YANG INKLUSIF PADA SISWA KELAS V SDN NGADIREJO - Danang Saputra; Dwi Nur Nikmah; Kharisma Firdaus (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to strengthen students’ democratic attitudes through the implementation of Problem Based Learning (PBL) on the topic of Pancasila Values, supported by group seating classroom management and academic supervision to create inclusive learning interactions in Grade V of SDN Ngadirejo. This research employed a descriptive qualitative approach using observation, interviews, and documentation as data collection techniques. The participants consisted of 23 students, including 8 boys and 15 girls. The research instruments included an observation sheet for democratic attitudes, a checklist for inclusive interaction, an assessment sheet for PBL implementation, and an academic supervision form. The findings indicate that the use of authentic problems in PBL effectively increases equal participation in group discussions, enhances students’ respect for differing opinions, and encourages decision-making through deliberation. The application of group seating successfully fostered more collaborative group dynamics, enabling students to interact more openly and supportively. Additionally, academic supervision helped teachers refine facilitation strategies, strengthen classroom management, and ensure that learning interactions remained inclusive for all students. Overall, the study concludes that the synergy between PBL, collaborative classroom management, and academic supervision is effective in promoting a democratic and inclusive learning culture in elementary schools.